Disposal of low activity radioactive waste - International Atomic Energy Agency (Vienna : International Atomic Energy Agency, 2005)
Redistribution or sale of any material on the CD-ROM in machine read able or any other form is prohibited.
Includes bibliographical references.
The Symposium was held in Cordoba, Spain from 13 th-17th, December 2 004.
CD-ROM.
Keywords: Radioactive waste disposal -- Safety measures -- Congresses; Radioactive waste disposal in the ground -- Safety measures -- Congr esses